INVESTIGATING THE IMPACTS OF SKYLINE ON SOCIO-ECONOMIC STATUS AND SOCIO-CULTURAL FABRIC OF HALA - Mahjabeen Memon; Ar Faryal Sikander2; Shazia Abro; Faiqa Khan (International Journal of Contemporary Issues in Social Sciences, 2024)
The research investigates the effects of alterations in skylines on the socio-economic and socio-cultural structures of Hala, a village located in Sindh province, Pakistan. The study focuses on how buildings and structures within Hala changed from being made using natural materials that were typical for construction to processed materials that are believed to be better in terms of quality and lasting power. Thus it shows how this shift in building practices has influenced local economies, cultural practices and societal relations. It also highlights the consequences of abandoning traditional construction methods and materials which were usually obtained from the environment surrounding them and merged seamlessly with their way of life and lifestyle. As an important strategy for maintaining economic growth and cultural identity, the preservation of such man-made places should therefore be ensured among others. This is because rapid modernization threatens to homogenize architectural styles further disrupting fragile local economies, cultures, even communities themselves. Hala is a village in which these issues are examined with respect to the transformation of its built environment and the growing importance of social, economic and cultural consideration for rural communities. This initiative aims at developing policies and practices that would enhance sustainable development in rural areas without altering their indigenous cultural heritage or social structures.